HASIL BELAJAR EKONOMI MELALUI METODE PROBLEM SOLVING DAN DISKUSI BERDASARKAN MOTIVASI SISWA - Marlena Marlena; R Gunawan Sudarmanto; Nurdin Nurdin (Faculty of Teacher Training and Education, University of Lampung, 2013)
This study aimed to determine: (1) the combined effect of the method of problem solving and discussion with high and low motivation, (2) the effect of the method of problem solving and discussion, (3) the effect of high and low motivation, (4) the interaction between problem solving methods and discussions with high and low motivation, and (5) learning method is more effective. The design of this research is experimental factorial approach. The results showed that: (1) there is no economic distinction antarmetode learning outcomes learning (problem solving and discussion) and antarmotivasi students (high and low) together, (2) there was no difference in learning outcomes between the learning economy by using methods problem solving and learning by using the method of discussion, (3) there are economic differences between students' learning outcomes that a high level of motivation and low motivation, (4) there is no significant interaction antarmetode learning (problem solving and discussion) and student motivation (high and low), (5) more effective problem solving methods used in carrying out the learning process of economic discussion on methods.Keywords: method of problem solving, discussion, and motivation